Morphometric brain measurement of prenatal ultrasound-induced rabbit fetus using Micro-Computed Tomography (Micro-CT) - Ahmad Zaiki, Farah Wahida; Dom, S. M. (Penerbit UTM Press, 2016)
Prenatal ultrasound is widely used and became an integral part of the clinical practice, particularly in obstetrics and gynecology. However, the advances in the capability of ultrasound equipment nowadays, trigger a greater image processing power, hence might as well increase the fetal exposure. Hence premises the morphometric brain measurement to be assessed in this study as an evidence of the ultrasound interruptions during the fetal neuronal development. This research randomly analyzed a total of 18 ultrasound-induced rabbit fetuses for fetal brain volume and surface after being exposed prenatally to the ultrasound exposure (duration=60 minutes; frequency = 7.09 MHz; spatial peak temporal average intensity (ISPTA) = 49.4 W/cm2; power = 56.0 W; thermal index (TI) = 0.2; mechanical index (MI) = 1.0). The fetuses were analyzed for morphometric brain measurement of brain volume and surface using Skyscan™ 1176 Micro-computed Tomography (Micro-CT). There were significant differences in the measurement of brain volume and surface at the 2nd and 3rd stage of gestation (P < 0.05). Results suggested that there are significant differences in the brain volume and surface between the controls and the 2nd and 3rd stage of gestation. There are also a significant reduction in the brain volume and surface in the exposed groups at all stages of gestation (P < 0.05).